Protection of baicalin against lipopolysaccharide induced liver and kidney injuries based on 1H NMR metabolomic profiling. Issue 4 (24th May 2016) - Liao, Shanting; Li, Pei; Wang, Junsong; Zhang, Qian; Xu, Dingqiao; Yang, Minghua; Kong, Lingyi
Abstract : LPS disturbed the metabolomic profiles in the serum, livers and kidneys of mice, and baicalin ameliorated these disturbances. Abstract : Severe sepsis and septic shock are common and lethal conditions characterized by a systemic inflammatory response that is activated by invasive infection. In this study, a lipopolysaccharide (LPS) induced sepsis mice model was established to investigate the toxicities of LPS and the therapeutic effect of baicalin. Sera for clinical biochemistry and NMR metabolomic investigation, and liver and kidney tissues for histopathological examination, molecular biology measurement and NMR metabolomic profiling were collected. Multivariate analysis of metabolic profiles of the serum, liver and kidney extracts of mice revealed the occurrence of a severe inflammatory response, oxidative stress, and perturbances in energy and amino acid metabolism in LPS induced sepsis mice, which could be greatly ameliorated by baicalin treatment. This integrated 1 H NMR based metabolomics approach gave us a new insight into the pathology of LPS induced sepsis, and helped in understanding the therapeutic effects of baicalin in a holistic view.